Pemanfaatan Google My Business Sebagai Alat Promosi UMKM pada Pembuatan Tempe di Desa Paya Gambar - Sunilfa Maharani Tanjung; M. Oemar Abdillah; M. Jaffar Rayhannur; Laura Melsya; Farhan Rusdy Asyhary Lubis; Usiono (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
This community service focuses on the development of micro, small and medium enterprises (MSMEs) “Tempe Endul” in Paya Gambar Village, Deli Serdang Regency. Previously, these MSMEs faced barriers to promotion and sales because they were not registered on Google My Business and did not use digital technology. The purpose of the service is to increase the visibility of MSMEs by registering them on Google My Business and provide support in implementing digital marketing strategies. Through mentoring, field observations and interviews, “Tempe Endul” MSMEs can understand the importance of digital marketing. Loyalty helps register these MSMEs on Google My Business and optimize their business profile with contact information, address, product photos, and customer reviews. As a result, this business is now shown on Google Maps with a clear address, opening hours and full contact details. Using Google My Business offers significant benefits. Customers can easily find and order Endul tempeh, and this MSME can enhance its positive image and revenue. The use of digital technology enables MSMEs to compete in the industry 4.0 era and expand their market reach. This service illustrates the importance of adopting digital technology to increase MSME competitiveness, overcome advertising limitations and boost the local economy. The result of this service has been increased visibility and performance of “Tempe Endul” MSMEs through the implementation of Google My Business. With the help of digital technology, MSMEs can optimize marketing activities, reach more customers, and increase revenue. This move reflects the strategic potential of MSMEs in supporting the local economy and overcoming obstacles encountered in the current era of digitalization.